The Effect of Rotina Product Quality on Consumer Satisfaction at PT. Tomo Food Industry - Solihin Royani; Wulan Indriani (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Food product industry has become one of the leading sectors as it fulfills a basic need. The rapid growth of the food business requires entrepreneurs to innovate and develop in order to sustain their businesses by improving product quality to achieve consumer satisfaction. PT. Tomo Food Industry, as one of the bread food companies, must be able to compete with similar product qualities to attain consumer satisfaction. Therefore, this research aims to identify and analyze the influence of Rotina product quality on consumer satisfaction at PT. Tomo Food Industry. The research method employed in this study is quantitative research with a survey approach using a Likert scale. A total of 50 respondents were involved in this research. Based on the data analysis results, it is revealed that Rotina Product Quality and Consumer Satisfaction at PT. Tomo Food Industry have a strong relationship. This is evidenced by the coefficient of determination test results, which obtained a value of 0.999 or 99.9%. Furthermore, there is a positive influence of Rotina Product Quality on Consumer Satisfaction at PT. Tomo Food Industry, as indicated by the hypothesis test results of the T-test with a calculated value of 301.805 > critical value 1.675. Therefore, it can be concluded that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted, which means there is a positive influence of Product Quality (X) on Consumer Satisfaction (Y) at PT. Tomo Food Industry